Structural insights in mammalian sialyltransferases and fucosyltransferases - Grewal, Ravneet Kaur (2021)
Funding Information: The APC was funded by King Abdullah University of Science and Technology. M.C.: L.C. and A.R.S. acknowledge the King Abdullah University of Science and Technology (KAUST) for support. We thank Romina Oliva, University of Parthenope (Naples), for helpful comments. Thanks to the STEMskills Research and Education Lab team members for support.